A metaethically based position on abortion and the concept of human dignity - Molina Castillo, Rafael Horacio (2020)
A common problem in moral discourse is the risk of incurring in infinite regressions. This, together with other criticisms also directed at scientific disciplines, motivated the sceptical attitude towards morality advised by several postmodern theories. The response of both moral philosophy and science was similar: to reaffirm the possibility of reaching agreements of “truth” or “correction” through rational discussion, which in turn implies a regulated procedure to submit theories to questioning in the freest possible way. In this paper the author intends to delineate some elements of rational discourse that are characteristically used in practical discourse, and then apply them to a discussion of abortion. The central purpose of this research consists in contributing to the analysis of the justifiability of the idea that the fetus can have dignity. This discussion implies first identifying a theory of dignity that appropriately satisfies the demand for universality of all rational discourse, and then applying it to some of the usual arguments in the abortion debate.